METABOLIC RESPONSES TO IN VITRO IN DROUGHT-TOLERANT IN A Cucurbita pepo L. ELICITED BY SALICYLIC ACID AND ZINC OXIDE NANOPARTICLES - Lama D. I.; S. I. Neamah (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This experiment was conducted to investigate the effect of different zinc oxide nanoparticle (ZnONPs) concentrations and salicylic acid (SA) on growth characteristics and antioxidant defence from Cucurbita pepo L. callus culture in response to drought stress conditions. The study included two levels of drought induced by sorbitol (0 and 20 g l-1), two concentration of SA (0 and 20 mg l-1), and four concentrations of ZnONPs (0, 100, 200, and 300 ppm). Drought stress by sorbitol showed negative effects on some characteristics of callus culture fresh weight (FW), dry weight (DW), and hydrogen peroxide (H2O2). The exogenous SA showed a positive in most characteristics except for DW, H2O2 and CAT. ZnONPs positively affected all study indicators on tissue culture under drought conditions. The exogenous of both SA and ZnONPs without sorbitol increased significantly in FW and DW. The SA and ZnO NPs with sorbitol increased significantly in biochemical characteristics such as H2O2, SOD, CAT, proline, and phenolic compounds such as coumaric acid, ferulic acid, caffeic acid, luteolin, and rutin.